MAC approaches to communication efficiency and reliability under dynamic network traffic in wireless body area networks: a review - Herculano, Jorge; Pereira, Willians; Guimarães, Marcelo; Cotrim, Reinaldo; de Sá, Alirio; Assis, Flávio; Macêdo, Raimundo; Gorender, Sérgio (Computing, 2024)
Wireless Body Area Networks (WBANs) are wireless sensor networks that monitor the physiological and contextual data of the human body. Nodes in a WBAN communicate using short-range and low-power transmissions to minimize any impact on the human body’s health and mobility. These transmissions thus become subject to failures caused by radiofrequency interference or body mobility. Additionally, WBAN applications typically have timing constraints and carry dynamic traffic, which can change depending on the physiological conditions of the human body. Several approaches for the Medium Access Control (MAC) sublayer have been proposed to improve the reliability and efficiency of the WBANs. This paper proposes and uses a systematic literature review (SLR) method to identify, classify, and statistically analyze the published works with MAC approaches for WBAN efficiency and reliability under dynamic network traffic, radiofrequency interference, and body mobility. In particular, we extend a traditional SLR method by adding a new step to select publications based on qualitative parameters. As a result, we identify the challenges and proposed solutions, highlight advantages and disadvantages, and suggest future works.